Sustainability and photocatalytic performance of MOFs: Synthesis strategies and structural insights - Sandhu, Zeshan Ali; Farwa, Umme; Danish, Muhammad; Raza, Muhammad Asam; Talib, Aqib; Amjad, Hifza; Riaz, Rukhmah; Al-Sehemi, Abdullah G. (Journal of cleaner production, 2024)
In the pursuit for sustainable and efficient photocatalyst, Metal-organic frameworks (MOFs) have developed as fascinating materials with remarkable potential for photocatalytic applications. Despite numerous research, certain challenges are still remained in their sustainability and catalysis applications. The physicochemical properties of MOFs, impacted their photocatalytic effect, as well as issues related to synthetic approaches. This work aims to address these gaps by investigating the synthetic strategies and structural modifications of MOFs to enhance their photocatalytic excellence. MOFs have attained consideration in the process of striving for a green synthetic method. The use of green synthesis approaches, depicted the use of renewable precursors and clean solvents, is a key factor in the successful development and improvement of MOFs. By employing the combination of advanced synthetic methods, solvothermal and post-synthetic modifications, this work will explore the impacts of these methods on the structural and photocatalytic performance. Such materials possess the facile nature that triggers the invention of devices with inflexible and efficient photocatalytic performance by manipulating light absorption, separation of charges, and catalytic activity. This work focuses on highlighting the most recent updates in the synthesis processes of MOFs, with an eye on their sustainability and possible impact on the structure characteristics, especially with attention to photocatalysis. [Display omitted] •The synthetic mechanism and recent advancements were explored.•New structural insights of Molecular Organic Framework are addressed.•Photocatalytic performance of the Molecular organic framework was subject of interest.•Sustainability of Molecular organic framework considering environmental impacts are elaborated.